Effects of biologics on reducing the risks of total knee replacement and total hip replacement in rheumatoid arthritis. (17th September 2021) - Chang, Yu-Sheng; Chen, Jin-Hua; Lin, Tzu-Min; Hsu, Hui-Ching; Chen, Wei-Sheng; Lin, Sheng-Hong; Kuo, Pei-I; Lin, Yi-Chun; Chang, Chi-Ching
Abstract: Objectives: RA damages the joints and increases the risks of total knee replacement (TKR) and total hip replacement (THR). However, the benefits of biologics in preventing TKR or THR remain unclear. Methods: This retrospective nationwide study used the 2000–2013 claims-based National Health Insurance dataset. Biologics are reimbursed for refractory cases. The risks of TKR and THR in the biologic cohort were compared with those of an age- and sex-matched csDMARD cohort. A multivariate Cox regression model was used to investigate the benefits of bDMARDs for TKR and THR. Results: TKR was performed in 5979 biologic cases and 11 958 matched controls, of which 249 (4.16%) and 871 (7.28%) cases received TKR, respectively. THR was performed in 6245 biologic cases and 12 490 matched controls, of which 159 (2.55%) and 516 (4.13%) cases had THR, respectively. The biologic cohort had significantly lower incidence rates of TKR (11.73 vs 16.33/1000 person-years, P  < 0.001) and THR (7.09 vs 9.16/1000 person-years, P  < 0.001). After adjustment for confounding factors, the regular bDMARD subgroup (average dose >0.95 defined daily dose/day) had significantly lower risks of TKR (aHR: 0.55, 95% CI: 0.38, 0.81) and THR (aHR: 0.63, 95% CI: 0.40, 0.98). Those without MTX use, with steroid use, with biologic switch, and overlapping antiphospholipid syndrome had significantly higher risks of TKR and THR. Conclusions: Compared with the csDMARD cohort, the risks of TKR and THR in the bDMARD cohort were the same as those in the low-to-moderate dose subgroups and significantly lower in those with regular bDMARD use.